Unveiling Recognition and Valuation: Unearthing Insights from Heritage Asset Accounting: Mengungkap Pengakuan dan Penilaian: Menggali wawasan dari Akuntansi Aset Warisan - Retno Wulandari; Heri Widodo (Procedia of Social Sciences and Humanities, 2021)
This research employs a phenomenological perspective to investigate the accounting treatment of Heritage Asset Candi Pari, delving into its recognition, recording, and reporting within financial statements. Through informant interviews and document analysis, this study follows a three-stage data analysis process encompassing reduction, display, and conclusion. The findings reveal that Candi Pari is recognized as a plant asset with deliberate absence of monetary valuation, rendering it non-tradable. Aligned with PSAP 07/2010, Section 69, the asset is duly recorded in non-monetary units. This research advances our understanding of Heritage Asset accounting, offering implications for financial reporting practices and heritage management strategies. Highlights: Phenomenological Exploration: Investigating Heritage Asset accounting through a phenomenological lens, unraveling nuances in recognition and valuation practices. Non-Monetary Valuation: Revealing deliberate non-assignation of monetary value to Heritage Asset Candi Pari, impacting its tradeability and financial representation. PSAP Compliance: Aligning with PSAP 07/2010, Section 69, the study underscores the recording of Heritage Assets based on non-monetary units, contributing to accounting standard adherence. Keywords: Heritage Assets, Accounting Treatment, Recognition, Valuation, Financial Reporting